2012
DOI: 10.1093/humrep/des411
|View full text |Cite
|
Sign up to set email alerts
|

Plasma adipokines and endometriosis risk: a prospective nested case-control investigation from the Nurses' Health Study II

Abstract: study question: Do higher leptin levels and lower adiponectin levels predict subsequent development of endometriosis? summary answer: Plasma leptin and adiponectin levels were not associated with laparoscopically confirmed endometriosis when collected prior to disease diagnosis.what is known already: Case-control studies have identified altered levels of the inflammatory adipokines leptin and adiponectin in women with endometriosis, but it remains unclear whether inflammation results in endometriosis or whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
(38 reference statements)
0
9
0
Order By: Relevance
“…Increased levels of leptin have been identified in serum and peritoneal fluid specimens from women with endometriosis for more than two decades [ 55 , 58 ]. The role of leptin in the establishment and propagation of endometriotic lesions has also been shown in experimental models [ 59 ], but case-control analysis within the large cohort of NHS II failed to show statistically significant associations between endometriosis and leptin, even after adjustment for BMI (RR 1.2, 955 CI 0.7–2.0, p 0.72) [ 60 ]. More recently, Rathore et al showed that women with endometriosis had higher peritoneal fluid concentrations of leptin as compared to nonendometriosis peers ( p 0.040) [ 54 ].…”
Section: Metabolic Surgery What It Is and How It Can Contribute To Endometriosis Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased levels of leptin have been identified in serum and peritoneal fluid specimens from women with endometriosis for more than two decades [ 55 , 58 ]. The role of leptin in the establishment and propagation of endometriotic lesions has also been shown in experimental models [ 59 ], but case-control analysis within the large cohort of NHS II failed to show statistically significant associations between endometriosis and leptin, even after adjustment for BMI (RR 1.2, 955 CI 0.7–2.0, p 0.72) [ 60 ]. More recently, Rathore et al showed that women with endometriosis had higher peritoneal fluid concentrations of leptin as compared to nonendometriosis peers ( p 0.040) [ 54 ].…”
Section: Metabolic Surgery What It Is and How It Can Contribute To Endometriosis Researchmentioning
confidence: 99%
“…Initial studies showed that adiponectin secretion was suppressed in the context of endometriosis, both in the peritoneal fluid [ 64 ] and serum [ 65 ]. Nevertheless, the large NHS II study did not reveal any significant associations between endometriosis and adiponectin (RR 0.8, 95% CI 0.5–1.2, p 0.48) or leptin-to-adiponectin ratio (RR 0.8, 95% CI 0.4–1.4, p 0.14) after adjustment for BMI [ 60 ]. Similarly, the study of Choi et al did not yield any difference in expression of adiponectin between ovarian endometrioma and normal endometrial tissue samples (31.8% vs. 42.9%, p 0.29) [ 61 ].…”
Section: Metabolic Surgery What It Is and How It Can Contribute To Endometriosis Researchmentioning
confidence: 99%
“…Contrasting evidence exists on prolactin, leptin, luteinizing hormone (LH), and adiponectin levels in endometriosis patients versus controls, showing either no difference, an increase (prolactin, leptin LH) or a decrease (adiponectin) [ 23 , 75 , 76 ]. No consensus exists on changes in steroid hormone levels [ 23 ].…”
Section: Blood Biomarkersmentioning
confidence: 99%
“…Interestingly, however, body size in childhood and from early to late adulthood seems to be inversely associated with endometriosis 5,6 . Moreover, a body fat distribution characterized by a low waist‐hip ratio (WHR) has more often been observed in affected women, 6,7 which is also supported by genetic studies 8 . These results, however, have been obtained from multiple study populations and with no distinction between endometriosis subtypes.…”
Section: Introductionmentioning
confidence: 98%